DEVELOPMENT OF ANALYTICAL METHOD FOR THE DETERMINATION OF TRIAZOLE AND PYRETROID PESTICDES IN MUSTARD GREENS (Brassicajuncea) - Giang Chau, Nguyen Dang; Minh Hieu, Nguyen Thi (Hue University Journal of Science: Natural Science, 2017)
Triazole and pyrethroid are two of the most commonly used pesticides in vegetable cultivation nowadays. In this study, a multi-residue analytical method employing gas chromatography-mass spectrometry (GC–MS) technique was successfully developed for the quantification of two triazole fungicides, namely propiconazole and difenoconazole, and pyrethroid insecticide cypermethrin (including 4 isomers) in mustard greens. The GC–MS running program performed good separation with a low detection limit and short analysis time (24 minutes). Target compounds in mustard green samples were ultrasonically extracted in 15 minutes with 60 mL acetone, followed by clean-up steps using solid phase extraction in a packed activated carbon column with 40 mL acetone:toluene (v:v, 1:1) for elutions, and florisil cartridge with an elution mixture of 15 mL acetone:n-hexane (v:v, 1:5). The method quality control was conducted before applying for a preliminary screening of triazole and pyrethroid residue levels in mustard greens collected in Phu Yen province, Vietnam.